Integration of small RNA, degradome, and transcriptome sequencing data illustrates the mechanism of low phosphorus adaptation in Camellia oleifera - Chen, Juanjuan; Han, Xiaojiao; Ye, Sicheng; Liu, Linxiu; Yang, Bingbing; Cao, Yongqing; Zhuo, Renying; Yao, Xiaohua (Frontiers in Plant Science, 2022)
Phosphorus (P) is an indispensable macronutrient for plant growth and development, and it is involved in various cellular biological activities in plants. Camellia oleifera is a unique high-quality woody oil plant that grows in the hills and mountains of southern China. However, the available P content is generally deficient in southern woodland soil. Until now, few studies have focused on the regulatory functions of microRNAs (miRNAs) and their target genes under low Pi stress. In this study, we integrated small RNA, degradome and transcriptome sequencing data to investigate the mechanism of low Pi adaptation in C. oleifera. We identified 40,689 unigenes and 386 miRNAs by deep sequencing technology, and divided the miRNAs into four different groups. We found 32 miRNAs which were differentially expressed under low Pi treatment. A total of 414 target genes of 108 miRNAs were verified by degradome sequencing. Gene ontology (GO) functional analysis of target genes found that they were related to signal, response to stimulus, and transporter activity, indicating that they may respond to low Pi stress. The integrated analysis revealed that 31 miRNA-targets pairs had negatively correlated expression patterns. A co-expression regulatory network was established based on the profiles of the differentially expressed genes. Three hub genes (ARF22, WRKY53, SCL6), which were the targets of differentially expressed miRNAs, were discovered. Our results showed that integrated analyses of the small RNA, degradome and transcriptomics sequencing data provided a valuable basis for investigating low Pi in C. oleifera, and offer new perspectives into the mechanism of low Pi tolerance in woody oil plants.